Importance of Management Competencies in Organizations - Pahuachón Huayta, Oscar Fernando (2023)
The current dynamics of organizations has evidenced the need for professionals who are trained to work in complex environments, cooperate in multidisciplinary teams, accept assignments beyond their competencies and operational duties, and project strategies that help them reach their objectives. The aim of this article is to review the way in which management has moved from deeply focusing on tasks, organization, work teams, environment and technology to emphasizing competitiveness. Similarly, it has moved from focusing on operations-level work relationships, the formal and informal organization, management functions and styles, open systems, and environmental and technological analysis to organizational learning and intellectual capital. This evidences the need to continue managing and developing management competencies tor complex and volatile business environments.